Pengaruh Level Dosis Hormon Perangsang Yang Berbeda Pada Pemijahan Ikan Betok (Anabas testudineus Bloch) Di Media Air Gambut - Muhamad Noor Yasin (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Giving ovaprim with different dose levels in the spawning process will affect gonadal maturation process through the control of GnRH and LH release, which hypothalamic GnRH release, further work secreting pituitary luteinizing hormone (LH) which will trigger the final maturation of steroid hormone to gonads. This study aims to determine the effectiveness of LHRHa + stimulant contained in ovaprim with different dose levels in the process of spawning Climbing perch in the peat water. The study design using a completely randomized design for Climbing perch gonadal maturation studies using ovaprim with 4 treatments ( 1 ml , ½ ml, ¼ ml , and 0 ml / kg body weight). The results of the study showed is best to use a dose ¼ ml/kg body weight, that can increase starting time for courtship and spawning (3:30 and 4:30 hours), increase the value of Gonado Somatic Index (GSI) of 3.09% and increase frequency distribution of end fish eggs diameter 0.70 mm of 67.50%.